2012
DOI: 10.1016/j.cct.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

An EMR-based tool to support collaborative planning for medication use among adults with diabetes: Design of a multi-site randomized control trial

Abstract: Patients with type II diabetes often struggle with self-care, including adhering to complex medication regimens and managing their blood glucose levels. Medication nonadherence in this population reflects many factors, including a gap between the demands of taking medication and the limited literacy and cognitive resources that many patients bring to this task. This gap is exacerbated by a lack of health system support, such as inadequate patient-provider collaboration. The goal of our project is to improve se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Advancements in health information technologies such as virtual health coaches, patient portals, and interactive videos that support patient shared decision-making are providing new opportunities to prepare patients to be informed, activated partners in their care. [44–46] The Video Doctor multimedia tool is an example of one such intervention that has been shown to increase patient participation in the medical visit as well as improve lifestyle behaviors (e.g., reduce smoking, increase exercise and healthy eating) in a variety of patient populations. [45]…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in health information technologies such as virtual health coaches, patient portals, and interactive videos that support patient shared decision-making are providing new opportunities to prepare patients to be informed, activated partners in their care. [44–46] The Video Doctor multimedia tool is an example of one such intervention that has been shown to increase patient participation in the medical visit as well as improve lifestyle behaviors (e.g., reduce smoking, increase exercise and healthy eating) in a variety of patient populations. [45]…”
Section: Discussionmentioning
confidence: 99%
“…Based on an approach used by members of our study team and in other randomized clinical trials, demonstrated proper use was evaluated by having participants demonstrate exactly how they take each medication on a daily basis. For this task, participants placed beads that represented their pills into a dosing tray with 24 compartments, each compartment representing 1 hour of the day .…”
Section: Methodsmentioning
confidence: 99%
“…E‐prescribing has default instructions at the time of order. Electronic health record tools help standardize prescribing and structure physician counseling 12‐14 …”
Section: Discussionmentioning
confidence: 99%
“…Electronic health record tools help standardize prescribing and structure physician counseling. [12][13][14] Several bodies detail best practices for patient-centered prescription labeling. 15,16 Reducing variability and vagueness of instructions limits confusion.…”
Section: Discussionmentioning
confidence: 99%